Edoxaban administration following enoxaparin: A pharmacodynamic, pharmacokinetic, and tolerability assessment in human subjects - Zahir, Hamim; Matsushima, Nobuko; Halim, Abdel-Baset; He, Ling; Zhang, George; Lee, Frank; Worland, Valerie; Mendell, Jeanne (Thrombosis and Haemostasis, 2012)
Edoxaban is an oral direct factor (F)Xa inhibitor in advanced stages of clinical development. The primary objective of the present study was to assess the pharmacodynamics (PD) and safety of enoxaparin 1 mg/kg followed 12 hours (h) post-dose by edoxaban 60 mg, which is the regimen being used in the phase III study of edoxaban for the treatment of venous thromboembolism (Hokusai-VTE). This was a phase I, open-label, randomised, four-period, four-treatment cross-over study. Treatments were edoxaban alone (EDOX), enoxaparin alone (ENOX), edoxaban plus enoxaparin (EDOX+ENOX), and enoxaparin followed by edox aban 12 h later (ENOX12-EDOX). Serial blood samples were collected for PD (thrombin generation, anti-FXa) and pharmacokinetic (PK) variables (edoxaban and its principal metabolite M4 by LC-MS/MS, and anti-FIIa as a surrogate of enoxaparin). The highest effect on thrombin AUC (endogenous thrombin potential, or ETP), thrombin (peak), thrombin generation lag time, and velocity index was observed for EDOX+ENOX, followed by ENOX, ENOX12-EDOX, and EDOX. The greatest effect on anti-FXa activity was observed for EDOX+ENOX, followed by ENOX12-EDOX. As expected, neither edoxaban nor enoxaparin significantly altered the PK of the other drug. There were no serious adverse events during the study. It is concluded that a 60-mg dose of edoxaban can be safely administered 12 h following enoxaparin 1 mg/ kg.
Keywords: Edoxaban; enoxaparin; pharmacodynamics; pharmacokinetics